SUCCESS FACTORS IN GROWING SMBs: A STUDY OF TWO INDUSTRIES AT TWO STAGES OF DEVELOPMENT - Tor Jarl Trondsen, (Asian Academy of Management Journal, 2002)
The study attempts to identify factors for growing SMBs. An evolutionary phase approach has been used. The study also aims to find out if there are common and different denominators for newer and older firms that can affect their profitability. The study selects a sampling frame that isolates two groups of firms in two industries at two stages of development. A variety of organizational and structural data was collected and analyzed. Amongst the conclusions that may be drawn from the study are that it is not easy to find a common definition of success, it is important to stratify SMBs when studying them, an evolutionary stage approach helps to compare firms with roughly the same external and internal dynamics and each industry has its own set of success variables. The study has identified three success variables for older firms that reflect contemporary strategic thinking such as crafting a good strategy and changing it only incrementally, building core competencies and outsourcing the rest, and keeping up with innovation and honing competitive skills.